Diversity in underutilized plant species: an Asia-Pacific perspective - Arora, R.K. (Bioversity International, 2014)
This publication deals with the enumeration of 778 species of underutilized and less known minor food plants grown in different regions of Asia-Pacific. Information presented has been classified under use-based categories such as cereals/pseudocereals, grain legumes/pulses, roots, tubers, vegetables, fruits, nuts, and those providing spices, condiments, and of multi-purpose use including agroforestry species and environment friendly species. The choice for the priority species for R&D needs has been suggested/discussed and the role of native/ endemic diversity dealt with. Also information has been added to provide relative analysis of food/nutritional values of selected underutilized species. A thoughtprovoking need-based focus is also given for the use of other disciplines in meeting the growing need to promote and assess this diversity: use of biotechnology, ethnobotany and documenting indigenous knowledge, diverse uses and conservation of such species. The greater need for partnership/networking at national, regional and international level for realizing the full potential of underutilized species has been stressed to address the Millenium Development Goals (MDGs).